Physical properties and electrical aging effects in Fe3+/Nb5+hybrid-doped barium titanate ceramics - S. Prasertpalichatr (2018)
It is well known that acceptor and donor doping results in opposite ferroelectric aging effects; however, the aging effects in hybrid-doped (acceptor+donor) materials has remained mysterious. Thus, the aging behavior of dielectric and ferroelectric properties in Fe3+/Nb5+ hybrid-doped BaTiO3 ceramics was investigated in this study. The concentration of acceptor dopant (Fe3 +) was fixed at 1 mol%, while that of donor dopant (Nb5+) was varied from 0.5-2.0 mol%. The SEM and XRD techniques were used to study the microstructure and phase formation, respectively. The results showed that the dielectric properties of all de-aged samples decreased exponentially with time. The aged samples with 0.5 and 1.0 mol% Nb5+ obviously showed constricted hysteresis loops, while those with higher concentration of Nb5+ (1.5-2.0 mol%) showed normal hysteresis loops. The explanations based on the effects of defect dipole were discussed. Copyright © Taylor & Francis Group, LLC.